Effect of methane doping on nascent soot formation in ethylene-based laminar premixed flames. (15th December 2016) - Shao, Can; Guan, Bin; Lin, Baiyang; Gu, Hao; Gu, Chen; Li, Zhongzhao; Lin, He; Huang, Zhen
Highlights: The particle size distribution functions of soot particles in methane-doped ethylene flames behave bimodality. The number densities in downstream zone of the methane-doped flames are much higher than pure flame. Small ratio of methane doping can promote the volume fractions, while in large ratio cannot. Abstract: The impact of methane doping on sooting behavior of ethylene-base burner stabilized stagnation (BSS) flames was investigated by following the evolution of particle size distribution functions (PSDFs) of nascent soot. The M-series of flames with the equivalence ratio of 2.07 was doped by methane with the mixture ratio of 5%, 10% and 40%. All the methane-doping flames showed obvious bimodality in the PSDFs, and more particles in nucleation stage than the C3 reference flame. The synergistic effect appeared in small ratio (5% and 10%) methane doping cases, leading to the increase of the soot number density and soot mobility volume fractions. While the synergistic effect was not found under large methane doping condition (40%), in which the mobility volume fraction was less than that in C3 flame. By calculating the key species and analyzing the reaction pathways of pyrene formation with KM2-Mech, we found that small ratio of methane doping benefits C3H3 and pyrene (A4) formation, which strengthened the sooting tendency. However too much methane doping reduced the yield of C2H2 that is a critical intermediate of PAHs formation, leading to a lower sooting tendency compared with the pure ethylene flame.